2006
DOI: 10.1111/j.1600-0463.2006.apm_333.x
|View full text |Cite
|
Sign up to set email alerts
|

Nontypeable Haemophilus influenzae strains with the capsule‐associated insertion element IS1016 may mimic encapsulated strains

Abstract: With the elimination of Haemophilus influenzae type b through vaccination, it has been suggested that other types of H. influenzae strains might acquire virulence traits and emerge as important pathogens. The gene sequence IS1016 has been associated with an increased capacity to cause severe infections. It is usually present in encapsulated strains but is sometimes harbored by nontypeable H. influenzae strains. To explore this further, 118 H. influenzae isolates, collected from both patients and healthy carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…This isolate also possessed hia and was absent for hmw genes, similar to other IS1016-positive invasive NTHi from previous studies [29,31]. IS1016 has been linked with the capacity to cause severe infections [32] and Satola et al [31] also observed a statistically significant association between younger age and the presence of IS1016 in invasive NTHi. Hi26 was isolated from a 3-year-old patient.…”
Section: Detection Of Capsule-related Genes In Sequenced Isolatessupporting
confidence: 82%
“…This isolate also possessed hia and was absent for hmw genes, similar to other IS1016-positive invasive NTHi from previous studies [29,31]. IS1016 has been linked with the capacity to cause severe infections [32] and Satola et al [31] also observed a statistically significant association between younger age and the presence of IS1016 in invasive NTHi. Hi26 was isolated from a 3-year-old patient.…”
Section: Detection Of Capsule-related Genes In Sequenced Isolatessupporting
confidence: 82%
“…In F3031, HIBPF06250 is interposed between tabA1 and IS 1016 (Figure 7), and the gene (like the insertion sequence) is absent in F3047. Association of IS 1016 , first described as the Haemophilus capsulation locus–associated insertion sequence, with unusual and invasive virulence of NTHI strains has been suggested elsewhere ( 17 , 18 ), although no specific gene association has been identified.…”
Section: Resultsmentioning
confidence: 99%
“…Various other BPF-specific outer membrane proteins potentially involved in host–pathogen interactions have been identified, including a partially characterized hemagglutinin ( 14 ) and an ≈145-kDa phase-variable protein eliciting protective immunity ( 15 ), but none have been fully characterized, and their role in disease has not been established. Hae BPF (but not other Hae strains) has a copy of the Haemophilus insertion element IS 1016 ( 16 ), which has been implicated in acquisition of capsulation genes and other unspecified virulence factors in other H. influenzae strains ( 17 , 18 ), but its role has not been defined.…”
mentioning
confidence: 99%
“…An appreciable number of NTHI isolates show partial hybridization with cap locus sequences, most notably cap-associated IS1016, suggesting a relationship to encapsulated ancestors (36,53,60). Residual IS1016 sequence was found in a highly virulent NTHI strain, R2866 (INT1) (http://www.ncbi .nlm.nih.gov/genomes/lproks.cgi) isolated from a child with meningitis (20,21,46).…”
Section: Discussionmentioning
confidence: 99%